How Tzetzes lost his horse at Troy: metalepsis in the Carmina Iliaca - Lauxtermann, MD (Duke University Press, 2023)
When Tzetzes intrudes into the text a curious autobiographical aside, this is a good example of metalepsis, and its historical context can be discerned.